1980
DOI: 10.1071/bi9800027
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Antibodies to the Antigens of Lucilia Cuprina in the Sera of Fly-Struck Sheep

Abstract: A solid-phase radioimmunoassay was used to demonstrate that sheep with myiasis caused by the larvae of the Australian sheep blowfly, L. cuprina, had serum IgG antibodies to antigens present in an extract of the ground-up larvae. Previously struck animals demonstrated a more severe myiasis than their unstruck counterparts when both groups were subjected to a standard larval challenge. The effects of immunosuppressive therapy were expressed in terms of a decrease in the total number of larvae growing to maturity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…The high levels of L 1 H antibody in a few of the lambs suggests that some individuals may have experienced covert flystrikes or exposure to cross reacting antigens. The background L 1 H antibody level in the lambs is most likely due to cross reacting or natural antibodies to L. cuprina (O'Donnell et al 1980, Sandeman et al 1985, Skelly & Howells 1987, which have been found to be predominantly of the IgM isotype (Seaton et al 1992). Chin & Watts (1991) found higher serum antibody levels in the Trangie R compared with S animals following three intradermal vaccinations with Ps.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The high levels of L 1 H antibody in a few of the lambs suggests that some individuals may have experienced covert flystrikes or exposure to cross reacting antigens. The background L 1 H antibody level in the lambs is most likely due to cross reacting or natural antibodies to L. cuprina (O'Donnell et al 1980, Sandeman et al 1985, Skelly & Howells 1987, which have been found to be predominantly of the IgM isotype (Seaton et al 1992). Chin & Watts (1991) found higher serum antibody levels in the Trangie R compared with S animals following three intradermal vaccinations with Ps.…”
Section: Discussionmentioning
confidence: 94%
“…The intradermal inflammatory response to L. cuprina in these sheep has the dynamics of an Arthus (Type 3) hypersensitivity response, but has also been demonstrated in blowfly naive animals ), suggesting an innate inflammatory response. However, the question of acquired vs innate resistance in the R and S animals remains obscured, since every experiment that has investigated antibody responses to L. cuprina has detected antibodies that recognise L. cuprina larval homogenates in the sera of blowfly naive animals (O'Donnell et al 1980, Sandeman, Dowse & Carnegie 1985, Skelly & Howells 1987, Seaton et al 1992.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These humoral responses have been shown to be directed against E/S products of the larvae (42,43) and the salivary antigens (37) following natural infection, while the response has been characterized by the production of IgG (36,41) with subsequent analysis identifying a number of isotypes including IgG1, IgG2, IgA and IgM (44) and IgE (45) with the primary isotype being identified as IgG1 (42).…”
Section: Sheep Blowfly Infectionsmentioning
confidence: 98%
“…The humoral immune responses to infection was first reported back in the early 1980s (36), and several groups have further investigated the nature of both the systemic and local humoral response during infection (28,(37)(38)(39)(40)(41). These humoral responses have been shown to be directed against E/S products of the larvae (42,43) and the salivary antigens (37) following natural infection, while the response has been characterized by the production of IgG (36,41) with subsequent analysis identifying a number of isotypes including IgG1, IgG2, IgA and IgM (44) and IgE (45) with the primary isotype being identified as IgG1 (42).…”
Section: Sheep Blowfly Infectionsmentioning
confidence: 99%